Urban headway and upward mobility in India - Mitra, Arup (Cambridge : Cambridge University Press, 2020)
Urbanisation in the literature of development economics is expected to bring in a spectrum of social and economic transformations. With this framework in mind, this book focuses on various aspects of urbanisation in India and its impact on socio-economic variables. The study has been conducted at various levels of disaggregation such as state, district and city and the data is sourced from population census, NSSO's surveys on employment-unemployment schemes and results and consumption expenditure, and primary surveys on slum households conducted by the author. Urbanisation is studied as a process particular to developing countries, contextualising it within the study of India. While this brings about gradual changes contributing to overall growth, the pace is remarkably slow. It brings to the forefront the resilience of the social system that can be mitigated through significant interventions into some of the economic variables. Various policy implications of the evidence based research are discussed at the end of each chapter.
Title from publisher's bibliographic system (viewed on 04 May 2020).
Keywords: Urbanization -- India; Urban policy -- India